2020
DOI: 10.3390/ijms21186666
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Muscarinic Receptors in Human Schwann Cells

Abstract: Functional characterization of muscarinic cholinergic receptors in myelinating glial cells has been well described both in central and peripheral nervous system. Rat Schwann cells (SCs) express different muscarinic receptor subtypes with the prevalence of the M2 subtype. The selective stimulation of this receptor subtype inhibits SC proliferation, improving their differentiation towards myelinating phenotype. In this work, we describe for the first time that human SCs are cholinoceptive as they express several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 34 publications
(64 reference statements)
2
18
0
1
Order By: Relevance
“…Schwann cells are the main glial cells in the PNS and play an essential role in the insulation of axons by forming myelin, resulting in fast propagation of action potentials. Schwann cells also express the M1–M4 subtypes of muscarinic receptors on their membrane 10 , 11 . The muscarinic receptor type expressed on Schwann cells could differently mediate Schwann cell proliferation through M1 and/or M3 or differentiation, but mainly through the M2 subtype 17 , 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schwann cells are the main glial cells in the PNS and play an essential role in the insulation of axons by forming myelin, resulting in fast propagation of action potentials. Schwann cells also express the M1–M4 subtypes of muscarinic receptors on their membrane 10 , 11 . The muscarinic receptor type expressed on Schwann cells could differently mediate Schwann cell proliferation through M1 and/or M3 or differentiation, but mainly through the M2 subtype 17 , 19 , 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that this remyelination effect of clemastine is mediated by off-target antimuscarinic action at the muscarinic acetylcholine receptor on OPCs 6 , 9 . Schwann cells are the main glial cells in the PNS and also express M1, M2, M3, and M4 muscarinic receptors 10 , 11 . Clemastine is expected to promote Schwann cell-mediated myelin repair, as in previous reports of central nervous system (CNS) demyelinating disease.…”
Section: Introductionmentioning
confidence: 99%
“…All procedures were approved by the National Research Ethics Committee, the UK (NRES 18/NW/0847) and conformed with the World Medical Association Declaration of Helsinki. Primary naïve human SC were obtained as per Piovesana et al [ 17 ]. Briefly, nerves were dissected, and single extracted fibers were cut into small pieces, then cultured in 60 cm 2 dishes with SC media supplemented with 10 µM fsk and 100 ng/mL glial growth factor 2 (GGF-2, Acorda Therapeutics, Ardsley, NY, USA) for two weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies demonstrated that different neurotransmitters may control and modulate a variety of biological processes during development as well as adult life physiology [5][6][7]. In particular, it has been shown that both rat and human SCs express muscarinic acetylcholine receptors (mAChRs) and are thus able to respond to acetylcholine (ACh) stimuli [8][9][10][11]. The selective activation of specific mAChRs, such as the M2 subtype, regulates some aspects of the SCs development [8][9][10][11] as well as those mechanisms aimed at enhancing their regenerative capability, modulating the production and release of the nerve growth factor (NGF) [12].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been shown that both rat and human SCs express muscarinic acetylcholine receptors (mAChRs) and are thus able to respond to acetylcholine (ACh) stimuli [8][9][10][11]. The selective activation of specific mAChRs, such as the M2 subtype, regulates some aspects of the SCs development [8][9][10][11] as well as those mechanisms aimed at enhancing their regenerative capability, modulating the production and release of the nerve growth factor (NGF) [12]. Therefore, the cholinergic system could be a putative target for identifying novel pharmacological treatments to speed up the regeneration process.…”
Section: Introductionmentioning
confidence: 99%